Microbiology - Wessner, David R. 1963-; Dupont, Christine 1961-; Charles, Trevor 1963-; Neufeld, Josh D.
"Several features within the book will help our students understand and appreciate the science behind our knowledge. Each chapter begins with an opening vignette-a short story that frames a basic question within the context of both contemporary and historical issues-visually supported by a dynamic illustration. As the chapter unfolds, references back to the opening vignette are made repeatedly. At the conclusion of each chapter, an additional feature, The Rest of the Story, refers back to this opening vignette and art. This also ties into an active learning feature, Image in Action, that includes several critical-thinking questions. Each chapter contains a Mini-Paper, a synopsis of a scientific journal article that includes original data Questions for Discussion, and interactive online questions that focus on concepts and experimental design. Through the use of this feature, students will see how microbiologists ask intelligent questions, rationally design experiments, and evaluate data. In this edition, several new Mini-Papers have been included. Again, this feature will improve students' critical thinking skills and show them that our knowledge is evidence-based"--Provided by publisher.